Corneal protective effects of a new ophthalmic formulation based on vitamin B12 and sodium hyaluronate - Lazzara, Francesca; Conti, Federica; Maugeri, Grazia; D’Agata, Velia; Sotera, Ludovica; Bucolo, Claudio (Frontiers in Pharmacology, 2025)
IntroductionCorneal damage can happen due to a variety of insults, including environmental factors and iatrogenic issues. For instance, the corneal epithelium is sensitive to oxidative stress caused by reactive oxygen species (ROS) or by ultraviolet B (UVB) radiation. Moreover, the strictly correlated oxidative damage and inflammatory processes impair the corneal reparative wound healing mechanism. Corneal protection after damage remains an unmet medical need that requires urgent management. Sodium hyaluronate is known to protect the cornea against oxidative and inflammatory injury. Additionally, vitamin B12 is a good candidate for counteracting corneal damage, helping preserve visual functions.MethodsThe present study aimed to investigate the potential protective effect of an ophthalmic formulation based on 0.01% vitamin B12% and 0.15% sodium hyaluronate (DROPYAL EVO) compared to other ophthalmic formulations containing sodium hyaluronate and trehalose (TRIMIX and THEALOZ DUO). Two different in vitro models of corneal damage were carried out in corneal epithelial cells exposed to hydrogen peroxide (H2O2, 1 mM) or UVB (20 mJ/cm2). Cell viability, cytotoxicity, ROS production, and mRNA expression of pro-inflammatory cytokines (TNF-α and IL-1β) were assessed by MTT, LDH, 2′,7′–dichlorofluorescein diacetate (DCFDA) assays and Real-time PCR, respectively. Additionally, the ability of ophthalmic formulations to affect the wound healing process in corneal epithelial cells was assessed at different time points by scratch wound healing assay.ResultsThe eye drops containing vitamin B12 were able to significantly counteract oxidative and inflammatory damage in corneal epithelial cells exposed to H2O2 stimulus and UVB radiation, in terms of ROS production and pro-inflammatory cytokines expression. Additionally, the eye drops containing vitamin B12 obtained significantly better outcomes in terms of wound closure at 36 h and 48 h after scratching the corneal epithelial cells, compared to the other two formulations containing trehalose.DiscussionVitamin B12 potentially enhances the protective effect of sodium hyaluronate, accelerating the wound healing process and modulating oxidative stress and inflammation. Vitamin B12, in combination with sodium hyaluronate, could represent a promising approach to managing corneal epithelial damage. Further clinical investigations are needed to confirm this data.